1984
DOI: 10.1002/jcb.240250402
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of glycosaminoglycan production in murine tumors

Abstract: Three types of murine tumors, B-16 melanoma, A-10 carcinoma, and S-180 sarcoma, were shown to contain elevated glycosaminoglycan (GAG) concentrations in vivo as compared to normal muscle or subcutaneous tissue. Hyaluronate was especially concentrated in the A-10 carcinoma, which contained approximately six times more hyaluronate than subcutaneous tissue and 18 times more than muscle. In all three tumors, chondroitin sulfates, especially chondroitin-4-sulfate, were present in higher concentrations than in the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 29 publications
(12 reference statements)
3
15
0
Order By: Relevance
“…In the EGF induction CAT assays, transfected cells were equally divided, allowed to recover in complete medium for 24 h, and then treated with or without 10 nM EGF for an additional 24 h in 0.1% dialyzed fetal bovine serum containing medium. CAT activity was measured from cell extracts by the CAT Enzyme Assay System (Promega) based on liquid scintillation counting using 14 C-labeled chloramphenicol (Amersham) and n-butynyl coenzyme A. The level of CAT activity from pRVBCAT transfectants without EGF induction was set at 100% and the percent (fold) increase in the other transfectants determined and compared with the standard.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the EGF induction CAT assays, transfected cells were equally divided, allowed to recover in complete medium for 24 h, and then treated with or without 10 nM EGF for an additional 24 h in 0.1% dialyzed fetal bovine serum containing medium. CAT activity was measured from cell extracts by the CAT Enzyme Assay System (Promega) based on liquid scintillation counting using 14 C-labeled chloramphenicol (Amersham) and n-butynyl coenzyme A. The level of CAT activity from pRVBCAT transfectants without EGF induction was set at 100% and the percent (fold) increase in the other transfectants determined and compared with the standard.…”
Section: Methodsmentioning
confidence: 99%
“…Among the regulated genes are those encoding cell surface adhesion molecules (8 -10) as well as nuclear transcriptional factors that regulate gene expression. Cell surface glycoprotein CD44, an adhesion molecule that binds to the extracellular matrix components, hyaluronic acid (11) and osteopontin (12), has been postulated to modulate tumor invasion and metastasis (13)(14)(15). Our previous studies with mouse 3T3 fibroblasts demonstrated that EGF induced CD44 gene expression on both the protein and mRNA levels and that this was accompanied by enhanced cell attachment to the extracellular matrix component hyaluronic acid (16).…”
mentioning
confidence: 99%
“…Because tumors are frequently characterized by local accumulation of HA in vivo (Toole et al, 1979;Knudson et al, 1984), we stained sections from pancreata of RIP1-Tag2 transgenic mice, which spontaneously develop pancreatic tumors. Incubation of frozen sections from the pancreata of RIPTag2 mice with layilin-Fc showed positive staining of the ECM of the tumors ( Figure 5B), whereas no staining was observed with the E-cadherin-Fc control ( Figure 5A).…”
Section: Layilin-fc Binding To Tissue Sections Is Abolished By Hyalurmentioning
confidence: 99%
“…Because tumors are frequently characterized by local accumulation of HA in vivo (Toole et al, 1979;Knudson et al, 1984), we stained sections from pancreata of RIP1-Tag2 transgenic mice, which spontaneously develop pancreatic tumors.…”
Section: Layilin-fc Binding To Tissue Sections Is Abolished By Hyalurmentioning
confidence: 99%
“…Since one of the bik-binding proteins is identical to LP, which is apparently held at the cell surface by HA (19), it is reasonable to think that CD44 would be involved in this bik-mediated complex at the cell surface. It has been established that CD44 is a polymorphic integral membrane glycoprotein with a postulated role in matrix adhesion (23), lymphocyte activation (24 -26), lymph node homing (27), and tumor invasion (28,29) and metastasis (30). CD44 plays an important role in the physiology of normal and tumor cells (31,32).…”
mentioning
confidence: 99%